Boissevain, Jeremy. 2013. Factions, Friends and Feasts. Anthropological Perspectives on the Mediterranean. New York, Oxford: Berghahn Books. viii + 310 pp. Hb.: $95.00. ISBN: 9780857458445. - Kelemen, Petra (Array, 2014)
Book review: Boissevain, Jeremy. 2013. Factions, Friends and Feasts. Anthropological Perspectives on the Mediterranean. New York, Oxford: Berghahn Books.